The Qualification of Professional Liability as a Form of Legal Liability as Basis for an Approach to the Problem of Malpractice in Physical Education and Sport - Voicu, Alexandru-Virgil; Voicu, Bogdan-Iosif (Arena-Journal of Physical Activities, 2019)
The activity of physical education and sport has become, and needs to continue to be, an object of interest for legal practitioners and for those who wish to include this activity in the context and within the rigors of civilised conduct of the highest morality, but also in a strict legality and liability framework. The violation of certain rights inherent to human beings regarding their life, health, physical and mental integrity via professional errors (malpractice) manifested in the management, at different levels, of sporting activities, may cause injury to athletes and their dependants. This paper aims to present the liability of all the participants to sporting activities (including managers of sporting activities and organizations involved in these activities) regarding the impact of professional errors occurring in activities of physical education and sport - deeds which may give rise to legal liability, since professional liability, under the conditions of the new Romanian Civil Code and of relevant European Law, has become a form of civil liability.